CO2 Storage Potential Reconnaissance of the Newly Identified Red Beds of Hazlehurst in the Southeastern United States - Cao, Ruoshi; Knapp, James; Bikkina, Prem; Esposito, Richard (Frontiers in Energy Research, 2021)
The states of Georgia and South Carolina emitted ∼100 million tons (Mt) of CO2 in 2019 from point sources. Integration and interpretation of subsurface data enabled identification of a previously unrecognized, regionally extensive, and thick (up to 450 m) sedimentary sequence—the Red beds of Hazlehurst (RbH)—as a potential saline reservoir for CO2 storage in the southeastern United States. Based on the renewed stratigraphic framework and structural interpretation of the RbH interval, we analyzed detailed well logs and the depositional environments to provide reconnaissance-level regional scale estimations of the storage resource. The volumetric results suggest the effective storage area (∼85,000 km2) has a maximum resource potential for 390 gigatons (Gt) of anthropogenic CO2. Petrophysical measurements suggest the permeability of RbH ranges from 0.001 to 48 mD, and the porosity ranges from 11.1 to 18.4%. Residual/capillary trapping and solubility trapping act as the main trapping mechanisms for long term storage and prevent vertical migration of CO2 into the shallow freshwater aquifers. Due to the heterogeneity observed in geophysical logs and the scarcity of well penetrations, future data collection is needed to characterize the storage aquifer and confining aquitards of a site-specific system at this stage.